Association Between Gamma-Glutamyl Transferase Levels and Framingham-Estimated Cardiovascular Risk in Patients with Non-Alcoholic Fatty Liver Disease: A Cross-Sectional Study - M. C. Lalith Raja Deepak; S. Ashok Kumar; R. Elanchezian (International Journal of Health Sciences and Research, 2026)
Background: Non-alcoholic fatty liver disease (NAFLD) is a common cause of chronic liver test derangement and is closely linked to metabolic syndrome. Patients with NAFLD show a higher burden of cardiovascular risk factors than the general population. Gamma-glutamyl transferase (GGT), routinely measured as part of the liver panel, is a marker of oxidative stress and has been associated with cardiovascular morbidity in several population-based cohorts. Its association with calculated cardiovascular risk specifically in patients with NAFLD warrants further characterisation. Objective: To categorise patients with ultrasonographic evidence of fatty liver by grade of hepatic steatosis, estimate their serum GGT levels, and examine the association between GGT levels and 10-year cardiovascular risk estimated using the Framingham General Cardiovascular Disease Risk Score. Materials and Methods: This cross-sectional, single-centre study was conducted over six months (May–October 2017) among 100 consecutive patients with ultrasonographically confirmed fatty liver attending the Departments of General Medicine and Medical Gastroenterology, Government Stanley Medical College Hospital, Chennai. Fatty liver was graded (Grade 1–3) by abdominal ultrasonography, serum GGT was estimated using a standardised laboratory protocol (cut-off 45 IU/L, the institutional upper limit of normal), and 10-year cardiovascular risk was estimated using the Framingham General Cardiovascular Disease Risk Score, categorised as low (45 IU/L) in 73% of patients, with a mean value of 58.7 IU/L. Seventy-one percent of patients fell into the moderate-to-high Framingham risk category. Elevated GGT was significantly associated with moderate-to-high Framingham risk (84.9% vs 33.3% in the normal-GGT group; χ² = 25.49, p < 0.0001), with an odds ratio of 11.27 (95% CI 4.04–31.43) and a relative risk of 2.55 (95% CI 1.48–4.38). Neither smoking status (χ² = 0.15, p = 0.93) nor Framingham risk category (χ² = 0.86, p = 0.65) varied significantly by grade of hepatic steatosis. Conclusion: In this cross-sectional study, serum GGT was significantly associated with a higher calculated Framingham cardiovascular risk category in patients with NAFLD, independent of the grade of hepatic steatosis. As a single-centre, cross-sectional study without multivariable adjustment or prospective cardiovascular outcome data, these findings demonstrate an association rather than independent prediction of future cardiovascular events. GGT, being inexpensive and widely available, may nonetheless be a useful adjunct for cardiovascular risk assessment in NAFLD, pending validation in larger prospective studies. Key words: Non-alcoholic fatty liver disease; Gamma-glutamyl transferase; Framingham risk score; Cardiovascular risk; Fatty liver; Cross-sectional study